Reliability analysis of laterally loaded piles in marine environments considering the degradation of flexural rigidity. Issue 11 (4th November 2021) - Shao, Wei; Nie, Yinghui; Xu, Qiuhong; Shi, Danda
Abstract: In this paper, the governing equation of chloride diffusion in reinforced concrete square piles is presented. The deterioration process of a pile caused by chloride-induced reinforcement corrosion is analyzed. The time-varying degradation coefficient of the flexural rigidity of piles induced by reinforcement corrosion is obtained. The time-varying failure probability and reliability index under the displacement failure criterion are calculated by using the Monte Carlo simulation method. The sensitivity of the coefficient of variation (COV) and mean value of the significant parameters for the time-varying probability density function (PDF) curves is analyzed. The results indicate that the degradation coefficient of the flexural rigidity and the reliability index decrease with increasing service time, while the failure probability increases with increasing service time. The peak value of the PDF curve of the pile head displacement decreases as the COV of the lateral load, soil elastic modulus and mean value of the lateral load and bending moment increase. The displacement of the pile head corresponding to the peak value increases substantially with increasing lateral load and bending moment, and decreases significantly with increasing soil elastic modulus and concrete elastic modulus.